MEDIA SOSIAL DAN PEMBENTUKAN RELIGIUSITAS GENERASI Z META-ANALISIS - Miftahul Jannah; Nurmila (AN-NUR: Jurnal Pendidikan dan Pembelajaran, 2025)
The development of digital technology has influenced almost all aspects of human life, including the formation of religiosity among the younger generation. Generation Z, who were born and raised in the midst of the social media era, have undergone a transformation in understanding, expressing, and practicing religious values. This study aims to systematically review previous studies on the influence of social media on the religiosity of Generation Z using a meta-analysis approach. This research is descriptive-analytical in nature and focuses on synthesizing more than twenty scientific articles published between 2015 and 2023. The results of the study indicate that social media has a significant and complex impact. On one hand, social media increases access to religious knowledge, expands spiritual communities, and encourages more personal religious engagement. However, on the other hand, social media also poses serious challenges such as the simplification of religious teachings, the dominance of popular narratives with minimal scientific validation, and the emergence of phenomena such as spiritual anxiety (religious anxiety) and performative religious identity pressure. This study concludes that the formation of religiosity in the digital age cannot be separated from its accompanying epistemological, sociological, and psychological contexts. Therefore, a critical and contextual model of digital religious literacy is needed in Islamic religious education to ensure that Islamic values are instilled authentically and remain relevant for the digital generation.